Osteogenic Outcomes and Associated Modifiable Factors of 3D ‐Printed Individual Titanium Mesh Exposure: A Retrospective Analysis - Minxue Yang; Yaxin Bai; Yuling Yang; Yujie Zhu; Houqi Zhou; Yuanding Huang; Tao Chen (Clinical Oral Implants Research, 2026)
ABSTRACT Objective To identify independent risk factors for titanium mesh exposure following 3D‐printed individualized titanium mesh (3D‐PITM)‐assisted alveolar bone augmentation and to evaluate the impact of exposure on bone regeneration outcomes. Method This retrospective study included 52 patients with severe alveolar bone defects who underwent 3D‐PITM‐assisted guided bone regeneration (GBR) between January 2019 and August 2025, comprising 25 patients with mesh exposure and 27 without. Demographic characteristics and surgery‐related variables were collected; univariate analysis and multivariate logistic regression were performed to identify independent risk factors. Additionally, this study measured bone volume, bone height, and bone width at different time points to evaluate the impact of 3D‐PITM exposure on bone augmentation. Results The results showed that smoking, thin gingival biotype, and maxillary defects were significantly associated with mesh exposure ( p < 0.05): smoking (OR = 5.16, 95% CI: 1.28–20.82, p = 0.021), thin gingival biotype (OR = 4.21, 95% CI: 1.05–16.82, p = 0.042), and maxillary defects (OR = 11.49, 95% CI: 1.25–105.68, p = 0.031). Regarding bone augmentation, the exposure group showed significantly greater resorption in bone volume ( p = 0.0063), height ( p < 0.0001), and width ( p < 0.0001) than the nonexposure group. Moreover, early exposure resulted in more severe bone loss than late exposure across bone volume ( p = 0.0048), height ( p = 0.0019), and width ( p < 0.0001). Conclusion This study found that 3D‐PITM exposure significantly impairs bone regeneration, with smoking, thin gingival biotype, and maxillary defects identified as independent risk factors. Preoperative identification of these risk factors may help reduce mesh exposure and improve bone augmentation outcomes.